2017
DOI: 10.4103/ijd.ijd_380_16
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of skin adnexal tumors: A three year study of 110 cases at a tertiary care center

Abstract: Background:Skin adnexal tumors (SAT) encompass wide spectrum of benign and malignant tumors that differentiate toward one or more adnexal structures found in normal skin. Overall incidence of SATs is low yet they can be challenging to diagnose.Aims:The aim of this study is to study the spectrum and microscopic features of SATs.Materials and Methods:It was a retrospective cross-sectional, descriptive study conducted over a period of 3 years. Formalin fixed, paraffin-embedded sections were stained with hematoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 10 publications
11
29
1
Order By: Relevance
“…The most common anatomical site found to be head and neck region (53%) which was 22 out of 41 cases. Similar findings were observed by other studies conducted by Prasad BVS et al , Arora A et al, Gandhi R et al and Kaur K et al study [4,12,3,8].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most common anatomical site found to be head and neck region (53%) which was 22 out of 41 cases. Similar findings were observed by other studies conducted by Prasad BVS et al , Arora A et al, Gandhi R et al and Kaur K et al study [4,12,3,8].…”
Section: Discussionsupporting
confidence: 91%
“…This vaculolated cells had high N:C ratio, nuclear pleomorphism and bizarre hyperchromatic nucleus ( Figure 5). The study done by Kaur K et al found sebaceous carcinoma was common malignant adnexal tumour (19.64%) and the common age group was more than 60 years of age [8]. The Sebaceous Carcinoma characterized by tumour cells which showed irregular epithelial lobules with an infiltrating growth pattern in the dermis.…”
Section: Fig 4: A: 10 X Shows Trichoepithelioma B: 40x Shows Multiplmentioning
confidence: 97%
“…On the other hand, number of sebaceous tumor cases reported in this study was also low, with only 2 cases [11]. In a study with a larger series of 110 patients, follicular tumors (39.09%) were found to be the most common, followed by sweat gland tumors (37.27%), and sebaceous tumors (23.63%), respectively [12]. In our study, sebaceous hyperplasia (35.4%) was the most common case, followed by pilomatrixoma (24.6%) as the second most common case, whereas the most common malignant tumor case was extramammary Paget's disease.…”
Section: Discussioncontrasting
confidence: 61%
“…The female to male ratio in our study was 1.5. This rate was between 1.03 and 1.44 in most of the other studies, slightly in favor of male patients [6,7,10,12]. On the other hand, it has been reported in the Nair's study that CAT were seen 2.3 times more in female patients than in male patients [11].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation